Challenges in primary science : meeting the needs of able young scientists at Key Stage Two - Coates, David, 1948- (NACE-Fulton publication., 2003)
This practical and easy-to-use book enables teachers to challenge able children to develop their potential and to extend their thinking in primary science at Key Stage Two.